Comparative evaluation of enzyme and biocidal activity of Candida auris and Candida albicans - Nadezhda I. Ignatova; Maya I. Zaslavskaya; Natalya A. Alexandrova; Anna A. Lapshina; Tatyana V. Makhrova; Olga A. Lukova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2023)
Introduction. Secreted metabolites with enzymatic or toxic properties are important for effecting of Candida spp pathogenicity. The most clinically significant species is C. albicans. However, invasive infections associated with C. auris have a great significance.